A STEAM-Focused Program to Facilitate Teacher Engagement Before, During, and After a Fieldtrip Visit to a Children's Museum. (3rd July 2018) - Lawson, Chris A.; Cook, Mike; Dorn, Joe; Pariso, Bill
ABSTRACT: Annual fieldtrip visits offer an excellent opportunity to engage teachers and students in learning opportunities that may not otherwise be available in their classrooms. Here we describe a collaborative project designed to support teacher engagement before, during, and after a classroom fieldtrip to a children's museum. We found that providing a pre-visit lesson plan and in-class activities helped teachers recognize how an animation-based activity supported students' learning about STEAM concepts. Moreover, several teachers reported that the project inspired them, and gave them the tools, to think about ways to incorporate arts into their STEM curriculum. Overall, this project provides a framework for bridging formal and informal learning settings in a way that can help teacher connect the pedagogical goals of their classrooms with the educational goals of the museum.